Effectiveness of Action Observation and Motor Imagery on Relearning Upper Extremity Function After Stroke: A Systematic Review and Meta-analysis - Welage, Nandana; Bisssett, Michelle; Fong, Kenneth N.K.; Fahey, Paul; Coxon, Kristy; Liu, Karen P.Y. (International Clinical Neuroscience Journal, 2022)
The effectiveness of action observation (AO) and motor imagery (MI) in high-quality studies with less risk of bias is rarely reported together. This systematic review evaluates the effectiveness of AO and MI on improving upper extremity function among people after stroke by combining evidence of studies with high methodological quality. Randomised controlled trials, with a score of 6 or above in the PEDro Scale, that examined the effects of AO or MI for people with stroke were selected. A narrative analysis and meta-analysis were conducted using the PRISMA guidelines. Ten randomised controlled trials from 11 articles met the inclusion criteria. The results of meta-analysis showed that AO had a small to moderate statistically significant effect on improving upper extremity motor function (standardized mean difference, SMD = 0.34; confidence interval, CI = 0.08, 0.59; P = 0.35; I2 = 0.00%) and no significant effect on MI (SMD = 0.08; CI = -0.26, 0.42; P = 0.65; I2 = 0.00%) when compared with the control intervention. Evidence was found in support of AO and it is recommended for people with acute or sub-acute stroke.